Peran Koperasi Konsumen Pegawai Republik Indonesia (KK.PRI) dalam Meningkatkan Pemenuhan Kebutuhan Anggota SMPN 2 Tembung - Perkasa, Ripho Delzy; Fadlan, Izhar; Nisa, Khay Ratu (Ikatan Da'i Indonesia, 2024)
The Republic of Indonesia Employee Consumer Cooperative (KK.PRI) in developing its business has helped members meet their needs, and the problem that is not running smoothly is that cooperative members often make payments when they are due. These problems result in unstable cooperative finances and even make it difficult for members to take out loans at the cooperative. Therefore, the aim of writing this article is to (1) analyze the reasons why members (KK.PRI) often make payments due (2) identify solutions to members' problems. The subjects in this research are: (1) Chairman (2) Treasurer (3) Savings Staff. The Republic of Indonesia Employee Consumer Cooperative is located at Jl. Tembung Pasar VIII SMPN 2 Tembung. The results of this research show that the factors causing members to often make payments due are: (1) financial constraints, (2) lack of understanding regarding payment terms, (3) lack of commitment and contribution of members in their responsibilities, (4) prioritizing other payments. . The solutions to this problem are (1) Give members time to make payments. (2) Reminding members to make payments, (3) Directly deducting cooperative members' salaries (4) Strengthening regulations.